Association of Hepatocellular Carcinoma with Hepatitis B Virus Genotypes in Sana’a city – Yemen - Alariqi, Reem; Elham, Zeehrah; Al-Moyed, Khaled A.; Abdullah Gobara’a, Amatalkhaliq; Abdullah Al-Shehari, Wadee; El-Aghbary, Dekra; A. Al-Selwi, Abdul Hafeez (Journal of Medical Biomedical and Applied Sciences, 2020)
Hepatitis B remains a potentially Life-threatening infection in the liver caused by extremely infectious blood-born known as the Hepatitis B virus (HBV). HBV increases the risk of developing hepatocellular carcinoma (HCC). The virus can be divided into various HBV genotypes and sub-genotypes due to HBV’s high genetic diversity. In order to properly control HBV infection by medical staff and improve public health, an understanding of the distribution of HBV genotype has been of great importance. First our cross-sectional analysis was performed using a multiplex PCR technique to determine the association of HBV genotypes with HCC in Yemeni patients. Secondly, to determine the potential risk factors, including patient information, clinical data, and their association with HBV infection among these HCC patients in Sana’a city, Yemen. Eighty HCC patients clinically diagnosed with HCC were included in this study. They attended the National Oncology Center in Sana’a city during the period from September 2016 to September 2017; out of the 80 HCC patients, 37.5% had HBV detected by the HBV-DNA. D (36.7%) and A (26.7%) genotypes were reported as the predominant HBV genotypes, followed by B genotype, 20%, and mix genotypes that were16.6% among these HCC patients. The mean age of them was (58.7±16.8) years old, and were predominantly males 58(72.5%) versus females 22(27.5%). There was a statistically significant association between qat chewing, smoking, Shamah intake, and HBV infection. In contrast, there was no statistically significant association between blood transfusion, surgical and dental procedures, and HBV infectionHepatitis B remains a potentially Life-threatening infection in the liver caused by extremely infectious blood-born known as the Hepatitis B virus (HBV). HBV increases the risk of developing hepatocellular carcinoma (HCC). The virus can be divided into various HBV genotypes and sub-genotypes due to HBV’s high genetic diversity. In order to properly control HBV infection by medical staff and improve public health, an understanding of the distribution of HBV genotype has been of great importance. First our cross-sectional analysis was performed using a multiplex PCR technique to determine the association of HBV genotypes with HCC in Yemeni patients. Secondly, to determine the potential risk factors, including patient information, clinical data, and their association with HBV infection among these HCC patients in Sana’a city, Yemen. Eighty HCC patients clinically diagnosed with HCC were included in this study. They attended the National Oncology Center in Sana’a city during the period from September 2016 to September 2017; out of the 80 HCC patients, 37.5% had HBV detected by the HBV-DNA. D (36.7%) and A (26.7%) genotypes were reported as the predominant HBV genotypes, followed by B genotype, 20%, and mix genotypes that were16.6% among these HCC patients. The mean age of them was (58.7±16.8) years old, and were predominantly males 58(72.5%) versus females 22(27.5%). There was a statistically significant association between qat chewing, smoking, Shamah intake, and HBV infection. In contrast, there was no statistically significant association between blood transfusion, surgical and dental procedures, and HBV infection